1981
DOI: 10.2307/2937261
|View full text |Cite
|
Sign up to set email alerts
|

Intertidal Landscapes: Disturbance and the Dynamics of Pattern

Abstract: Abstract. The mussel Mytilus californianus is a competitive dominant on wave-swept rocky intertidal shores. Mussel beds may exist as extensive monocultures; more often they are an everchanging mosaic of many species which inhabit wave-generated patches or gaps. This paper describes observations and experiments designed to measure the critical parameters of a model of patch birth and death, and to use the model to predict the spatial structure of mussel beds. Most measurements were made at Tatoosh Island, Washi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
796
2
8

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,079 publications
(828 citation statements)
references
References 37 publications
22
796
2
8
Order By: Relevance
“…Valuable early contributions to the conceptualisation of ecological systems as "dynamic mosaics of patches" took place in benthic and pelagic marine environments (e.g. Levin and Paine, 1974;Steele, 1978;Paine and Levin, 1981;Sousa, 1984;. It is in terrestrial environments, however, that the quantification of landscape pattern and the study of the effect of pattern on ecological processes have made significant advances in understanding animal movement and persistence, the effects of disturbance, the importance of broad-scale environmental change and the design of resource management strategies (Turner, 1989;Saunders et al, 1991;Hobbs, 1994;Forman, 1995;Farina, 1998).…”
Section: Spatial Hierarchymentioning
confidence: 99%
“…Valuable early contributions to the conceptualisation of ecological systems as "dynamic mosaics of patches" took place in benthic and pelagic marine environments (e.g. Levin and Paine, 1974;Steele, 1978;Paine and Levin, 1981;Sousa, 1984;. It is in terrestrial environments, however, that the quantification of landscape pattern and the study of the effect of pattern on ecological processes have made significant advances in understanding animal movement and persistence, the effects of disturbance, the importance of broad-scale environmental change and the design of resource management strategies (Turner, 1989;Saunders et al, 1991;Hobbs, 1994;Forman, 1995;Farina, 1998).…”
Section: Spatial Hierarchymentioning
confidence: 99%
“…While this study and several others (Paine & Levin 1981, Schoener & Schoener 1981 imply that edge effects may influence rates of succession to the competitive dominant, the importance of edge effects to successional dynamics has received little investigation. It is clear that to gain a n understanding of patch dynamics in a number of systems it may b e necessary to subdivide our scales of observation a n d to study areas of habitat in finer detail.…”
Section: Edge Effectsmentioning
confidence: 70%
“…Keen & Neill 1980, Russ 1980, Chalmer 1982, however organisms can respond differentially to patches of habitat and thereby may exert potentially important 'edge effects'. Edge effects can result from patterns in the settlement of organisms (Bernstein & Jung 1979, Schoener & Schoener 1981, this study), and they have been shown to arise through the action of grazers in a number of systems (Randall 1965, Bartholomew 1970, Dayton 1971, Ogden et al 1973, Stimson 1973, Suchanek 1978, Paine & Levin 1981, Sousa 1984.…”
Section: Edge Effectsmentioning
confidence: 82%
See 1 more Smart Citation
“…which has been used by many authors in plant ecology (Nagano, 1978;Takada and Iwasa, 1986;Kohyama, 1992) as well as in various other fields of biology (Trucco, 1965;Shinko and Streifer, 1967;Levin and Paine, 1974;Paine and Levin, 1981;Kirkpatrick, 1984). Likewise, the Sharpe-Lotka-McKendrick-von Foerster equation is a particular version of the more general Fokker-Plank equation (also known as diffusion or Kolmogorov forward equation), which describes the moment dynamics of a probability distribution and has been used by Hara (1984b) and many others to incorporate the spatial and stochastic fluctuations of the size density distribution.…”
Section: Mathematical Modelmentioning
confidence: 99%